A Guide to the clinical care of women with HIV - Anderson, Jean, M.D.; United States. HIV/AIDS Bureau (Rockville, MD : HRSA, HIV/AIDS Bureau, 2001)
Contains information relating to general principles of medical care for HIV patients.
Title from disc label.
Includes bibliographical references and index.
Also available in print and online.
System requirements: 486MHZ Pentium processor; 16MB RAM; Windows 3.x or Explorer Windows; 2X CD-ROM drive.
Keywords: HIV-positive women; AIDS (Disease) in women; HIV Infections; Women -- Hygiene